Characterization of the ionosphere above the Murchison Radio Observatory using the Murchison Widefield Array - Jordan, C.; Murray, S.; Trott, Cathryn; Wayth, R.; Mitchell, D.; Rahimi, M.; Pindor, B.; Procopio, P.; Morgan, J. (Oxford University Press, 2017)
We detail new techniques for analysing ionospheric activity, using Epoch of Reionisation (EoR) datasets obtained with the Murchison Widefield Array (MWA), calibrated by the `Real-Time System' (RTS). Using the high spatial- and temporal-resolution information of the ionosphere provided by the RTS calibration solutions over 19 nights of observing, we find four distinct types of ionospheric activity, and have developed a metric to provide an `at a glance' value for data quality under differing ionospheric conditions. For each ionospheric type, we analyse variations of this metric as we reduce the number of pierce points, revealing that a modest number of pierce points is required to identify the intensity of ionospheric activity; it is possible to calibrate in real-time, providing continuous information of the phase screen. We also analyse temporal correlations, determine diffractive scales, examine the relative fractions of time occupied by various types of ionospheric activity, and detail a method to reconstruct the total electron content responsible for the ionospheric data we observe. These techniques have been developed to be instrument agnostic, useful for application on LOFAR and SKA-Low.